Ulrich Beck’s Thoughts and Ideas (The Theorist of Risk Society) - habib ahmadi; roudabeh dehghani (توسعه اجتماعی, 2016)
Ulrich Beck is one of the theorists who theorized about modernity. One of the concepts he developed, is idea of “risk and society”, which he first developed in his book “Risk Society”. He considers risk society through the rise of first and then second modernity; he knows 1970s as the period through which the second modernity arise. He considers risk society with three characteristics: 1. Further distribution of wealth. In Risk Society, it is the distribution of risk and bad that matters not distribution of wealth and good. 2. Individualism. In his view, individualism is the structure of second modernity, since 17 century the structures of society has been eroded in the benefit of autonomy and freedom of individuals; and individuals have to constitute their biographies. The freedom from structures of society is freedom toward uncertainties of a risk society. 3. Non standardization of work. All around the world, unstable work grows, and people are in the situation of uncertainty of work. With regard to what has been said, Risk Society includes changes which relate to each other in contemporary social life. Risk Society is the period of passage to second modernity from first modernity. Side effects arise from fast technical-scientific progresses lead to unbelievable results, for example economical dangers and so on. The concept of risk is based on the idea that modernization will bring up many problems which lead to reflexivity of social structures.